Low-intensity pulsed ultrasound rescues insufficient salivary secretion in autoimmune sialadenitis. Issue 1 (December 2015) - Sato, Minami; Kuroda, Shingo; Mansjur, Karima; Khaliunaa, Ganzorig; Nagata, Kumiko; Horiuchi, Shinya; Inubushi, Toshihiro; Yamamura, Yoshiko; Azuma, Masayuki; Tanaka, Eiji
Abstract Introduction Low-intensity pulsed ultrasound (LIPUS) has been known to promote bone healing by nonthermal effects. In recent studies, LIPUS has been shown to reduce inflammation in injured soft tissues. Xerostomia is one of the most common symptoms in Sjögren syndrome (SS). It is caused by a decrease in the quantity or quality of saliva. The successful treatment of xerostomia is still difficult to achieve and often unsatisfactory. The aim of this study is to clarify the therapeutic effects of LIPUS on xerostomia in SS. Methods Human salivary gland acinar (NS-SV-AC) and ductal (NS-SV-DC) cells were cultured with or without tumor necrosis factor-α (TNF-α; 10 ng/ml) before LIPUS or sham exposure. The pulsed ultrasound signal was transmitted at a frequency of 1.5 MHz or 3 MHz with a spatial average intensity of 30 mW/cm2 and a pulse rate of 20 %. Cell number, net fluid secretion rate, and expression of aquaporin 5 (AQP5) and TNF-α were subsequently analyzed. Inhibitory effects of LIPUS on the nuclear factor κB (NF-κB) pathway were determined by Western blot analysis. The effectiveness of LIPUS in recovering salivary secretion was also examined in a MRL/MpJ/lpr /lpr (MRL/lpr ) mouse model of SS with autoimmune sialadenitis. Results TNF-α stimulation of NS-SV-AC and NS-SV-DC cells resulted in a significant decrease in cell number and net fluid secretion rate (p < 0.01), whereas LIPUS treatment abolished them (p < 0.05). The expression changes of AQP5 and TNF-α were also inhibited in LIPUS treatment by blocking the NF-κB pathway. Furthermore, we found that mRNA expression ofA20, a negative feedback regulator, was significantly increased by LIPUS treatment after TNF-α or interleukin 1β stimulation (NS-SV-AC, p < 0.01; NS-SV-DC, p < 0.05). In vivo LIPUS exposure to MRL/lpr mice exhibited a significant increase in both salivary flow and AQP5 expression by reducing inflammation in salivary glands (p < 0.01). Conclusions These results suggest that LIPUS upregulates expression of AQP5 and inhibits TNF-α production. Thus, LIPUS may restore secretion by inflamed salivary glands. It may synergistically activate negative feedback of NF-κB signaling in response to inflammatory stimulation. Collectively, LIPUS might be a new strategic therapy for xerostomia in autoimmune sialadenitis with SS.